2013
DOI: 10.1111/opo.12101
|View full text |Cite
|
Sign up to set email alerts
|

Manufacturer changes lead to clinically important differences between two editions of the TNO stereotest

Abstract: This is the accepted version of the paper.This version of the publication may differ from the final published version. Abstract Purpose: Stereoacuity tests used in clinical practice should be repeatable and reproducible. However, it has been observed in a clinical setting that new editions of the TNO stereotest appear to give different values from those obtained using previous versions. The purpose of the present research was to investigate this observation. Methods: One hundred and twenty-one Dutch subjects, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
17
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 33 publications
2
17
0
3
Order By: Relevance
“…29,36 Average differences of 30 arcsec between various editions of the TNO have been reported before and have been related to differences in the printing process, however this has not yet been investigated for the 9th and 10th edition of the test that were used in our study. 37 Our results are also in congruence with a study by Gadia and colleagues who showed correspondence between stereo thresholds of Randot Circles and a software-based stereo acuity test. 38 The similar thresholds obtained with our local clinical, local psychophysical and global psychophysical stereotests indicate that the higher thresholds obtained with TNO, a clinical test for global stereopsis, cannot be attributed to increased difficulty of global stereopsis compared to local stereopsis, as has been suggested before.…”
Section: Discussionsupporting
confidence: 92%
“…29,36 Average differences of 30 arcsec between various editions of the TNO have been reported before and have been related to differences in the printing process, however this has not yet been investigated for the 9th and 10th edition of the test that were used in our study. 37 Our results are also in congruence with a study by Gadia and colleagues who showed correspondence between stereo thresholds of Randot Circles and a software-based stereo acuity test. 38 The similar thresholds obtained with our local clinical, local psychophysical and global psychophysical stereotests indicate that the higher thresholds obtained with TNO, a clinical test for global stereopsis, cannot be attributed to increased difficulty of global stereopsis compared to local stereopsis, as has been suggested before.…”
Section: Discussionsupporting
confidence: 92%
“…El éxito del tratamiento depende de una detección y de un tratamiento precoz durante la infancia. (1)(2)(3)(4)(5) Se considera de primordial importancia la detección temprana de las alteraciones visuales causales de la ambliopía, ya que su tratamiento es sólo efectivo durante la maduración del sistema visual en la infancia, evitando de esta forma las negativas consecuencias de una visión inadecuada en la etapa adulta.…”
Section: Introductionunclassified
“…El test TNO parece ser el más riguroso con un valor normal de 60" y un rango que va desde 15" a 240" [4] o 49±26.3" [3] pero nuestros resultados muestran que sólo el 75% de la población estudiada, independientemente del género, alcanza 60". A pesar de esto, se ha descrito que el nivel de estereoagudeza depende de la edición del test realizado [12]. Independientemente de esta variación, van Doorn et al [12] describió valores medios desde 30" a 60" coincidiendo con Rosner and Clift (n=20) y con Heron et al (n=51) [13,14] pero nuestros cortes de normalidad del 85% y del 95% establecen que los sujetos pueden alcanzar aproximadamente 120" y 240" respectivamente.…”
Section: Introductionunclassified
“…A pesar de esto, se ha descrito que el nivel de estereoagudeza depende de la edición del test realizado [12]. Independientemente de esta variación, van Doorn et al [12] describió valores medios desde 30" a 60" coincidiendo con Rosner and Clift (n=20) y con Heron et al (n=51) [13,14] pero nuestros cortes de normalidad del 85% y del 95% establecen que los sujetos pueden alcanzar aproximadamente 120" y 240" respectivamente. En relación al test de Titmus, el valor medio de 40", rango 40"-60", [4] y de 41±3" [3] se han descrito previamente pero estos valores tan restrictivos están lejos de los que nosotros hemos encontrado en este estudio.…”
Section: Introductionunclassified